Construções geométricas com régua e compasso como disciplina eletiva - Benigno, José Gilson de Souza (2022)
This work shows that "Geometric Constructions with Ruler and Compass as an Elective Subject", developed in the final years of elementary school, as well as in high school, can contribute to motivate the interest of teachers in relation to the Geometry curricular component and consequently expand its scope. mathematical knowledge. Learning mathematical concepts in a practical and interactive way makes the teaching-learning process more meaningful and enjoyable. The student who understands a generalization of a given mathematical knowledge, not only as a mere formalization, but who feels safe to justify with his own arguments the because of this synthesis, he becomes more confident and confident to use it in challenging situations in his daily life. Developing ability to perform geometric constructions using ruler and compass, demonstrating properties in quadrilaterals associated with cases of congruence between triangles, knowing geometric places, as well as their properties, are some of the objectives to be achieved with this educational work proposal. The theoretical foundation of this work is based on Van Hiele's geometric learning levels. During the elective, the student must experience the five levels presented by the Dutch researcher, that is, visualization, analysis, informal deduction, formal deduction and rigor, responsible for the entire production of a thought related to geometry. At the end of the elective, students in groups should state a theorem related to the study of geometry, present its demonstration and its applicability in a problem-situation of everyday life.